Politeness and Impoliteness Strategies in Requests in The Office and The IT Crowd TV Series - Risma Putri Windani; Zulfa Sakhiyya (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Politeness is one aspect in communication that helps people maintain harmony in interactions and avoid social conflicts. In performing speech act that is inherently face-threatening, such as request, politeness strategies are used to help minimizing the threat to the addressee’s face. This study explores the manifestation of politeness and impoliteness strategies in making requests portrayed in American TV Series The Office and British TV Series The IT Crowd along with the similarities and the differences between them. This study used qualitative research approach and content analysis method. By drawing on Brown and Levinson’s (1987) politeness strategies and Culpeper’s (1996) impoliteness strategies, findings show that the most frequently used politeness strategy in delivering requests is bald on-record in both series. Negative politeness emerges as the second most frequently used, followed by positive politeness, whereas off-record strategies are the least employed. In terms of impoliteness, the result shows that bald on-record impoliteness is the most frequently used super-strategy in both series and off-record impoliteness becomes the least employed super-strategy. Despite the similarities regarding the use of politeness and impoliteness, some notable differences were also observed. In The Office, there is greater variation of positive politeness strategies employed, whereas in The IT Crowd, the variation is more apparent in the use of negative politeness. Furthermore, other differences were also found regarding the second and third most common strategy of impoliteness. In The Office, negative impoliteness emerges as the second most commonly employed strategy, followed by positive impoliteness. Whereas in The IT Crowd, the second most used strategy is positive impoliteness, followed by negative impoliteness. These similarities and differences are related to the background culture and humor style of each series.